Pharmacogenetic testing for CYP2C19 gene polymorphism for optimization of using antiplatelet therapy in patients with ischemic heart disease - Карпенко, Олена Олександрівна (ScienceRise: Medical Science, 2016)
Clopidogrel is a one of most important antiplatelet preparations for patients with myocardium infarction (MI) but it has the different influence effects. The aim of this research was to assess the contribution of CYP2C19 gene polymorphism in inhibition of ADP-induced aggregation of platelets by clopidogrel. Methods. We examined 52 patients (26,9 % women), mean age – 66,6±7,8 years with verified diagnosis MI. All patients underwent coronarography, stenting of infarction-depending coronary artery. All patients were divided in two groups: I carriers of *1/*1 allele and II – carriers of *2allele. Results. *1/*1 polymorphism was determined in 82,5 % of patients. Gender analysis of spreading of CYP2C19 gene polymorphism indicates that among 14 examined women *1/*1 genotype was revealed in 78,6 % (n=11), *1/*2-*2/*2 genotype – in 21,4 % (n=3). Among 38 examined men *1/*1 genotype was revealed in 81,58 % (n=31), *1/*2-*2/*2 genotype - in 18,42 % (n=7). We did not find the essential differences in dependence of sex from CYP2C19 gene polymorphism. In the group I we revealed the more inhibited spontaneous aggregation (1,52±0,53 % against 7,7±2,24 %, р=0,0000672) and ADP-induced platelets aggregation (14,16±4,96 % against 21,78±7,77 %, р=0,0127). Any essential differences in aggregation, induced by arachidonic acid (AC) were not found between two groups (15,36±5,96 % against 16,22±3,23 %, р=0,57). Conclusions. The spreading of CYP2C19 gene polymorphism is almost equal among men and women. According to the main mechanisms of clopidogrel effect, inhibition of ADP-aggregation of platelets proves that *1/*1-carriers of CYP2C19 gene react to the clopidogrel therapy better. CYP2C19 gene polymorphism does not influence on AC-induced platelets aggregation